ImmunosuppressiveTherapies Differently Modulate Humoral- and T-Cell-Specific Responses to COVID-19 mRNA Vaccine in Rheumatoid Arthritis Patients - Picchianti-Diamanti, Andrea; Aiello, Alessandra; Laganà, Bruno; Agrati, Chiara; Castilletti, Concetta; Meschi, Silvia; Farroni, Chiara; Lapa, Daniele; Najafi Fard, Saeid; Cuzzi, Gilda; Cimini, Eleonora; Grassi, Germana; et al. (Frontiers in Immunology, 2021)
Objective: To assess in rheumatoid arthritis (RA) patients, treated with different immunosuppressive therapies, the induction of SARS-CoV-2-specific immune response after vaccination in terms of anti-Region-Binding-Domain (RBD)-antibody- and T-cell-specific- responses against spike, and the vaccine safety in terms of clinical impact on disease activity. Methods: Health care workers (HCWs) and RA patients, having completed the BNT162b2-mRNA vaccination in the last 2 weeks, were enrolled. Serological response was evaluated by quantifying anti-RBD antibodies, while the cell-mediated response by a whole-blood test quantifying the interferon (IFN)-γ-response to spike peptides. FACS analysis was performed to identify the cells responding to spike stimulation. RA disease activity was evaluated by clinical examination through the DAS28crp, and local and/or systemic clinical adverse events were registered. In RA patients, the ongoing therapeutic regimen was modified during the vaccination period according to the American College of Rheumatology indications. Results: We prospectively enrolled 167 HCWs and 35 RA patients. Anti-RBD-antibodies were detected in almost all patients (34/35, 97%), although the titer was significantly reduced in patients under CTLA-4-inhibitors (median: 465 BAU/mL, IQR: 103-1189, p<0.001) or IL-6-inhibitors (median: 492 BAU/mL, IQR: 161-1007, p<0.001) compared to HCWs (median: 2351 BAU/mL, IQR: 1389-3748). T-cell-specific-response scored positive in most of RA patients [24/35, (69%)] with significantly lower IFN-γ levels in patients under biological therapy such as IL-6-inhibitors (median: 33.2 pg/mL, IQR: 6.1-73.9, p<0.001), CTLA-4-inhibitors (median: 10.9 pg/mL, IQR: 3.7-36.7, p<0.001), and TNF-α-inhibitors (median: 89.6 pg/mL, IQR: 17.8-224, p=0.0020) compared to HCWs (median: 343 pg/mL, IQR: 188-756). A significant correlation between the anti-RBD-antibody titer and Spike-IFN-γ-specific T-cell response was found in RA patients (rho=0.432, p=0.009). IFN-γ T-cell response was mediated by CD4+ and CD8+ T cells. Finally, no significant increase in disease activity was found in RA patients following vaccination. Conclusion: This study showed for the first time that antibody-specific- and whole-blood spike-specific T-cell-responses induced by the COVID-19 mRNA-vaccine were present in the majority of RA patients, who underwent a strategy of temporary suspension of immunosuppressive treatment during vaccine administration. However, the magnitude of specific responses was dependent on the immunosuppressive therapy administered. In RA patients, BNT162b2 vaccine was safe and disease activity remained stable.